2014
DOI: 10.1016/j.addbeh.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of research network participation on the adoption of buprenorphine for substance abuse treatment

Abstract: There is a growing body of research supporting the use of buprenorphine and other medication assisted treatments (MATs) for the rapidly accelerating opioid epidemic in the United States. Despite numerous advantages of buprenorphine (accessible in primary care, no daily dosing required, minimal stigma), implementation has been slow. As the field progresses, there is a need to understand the impact of participation in practitioner-scientist research networks on acceptance and uptake of buprenorphine. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Although methadone and buprenorphine are effective OATs for management of OUD, they are controlled substances with limitations that include restricted access and availability (Sharma et al, 2017), potential for misuse and diversion (Soyka, 2014), and barriers to acceptability in certain arenas, such as criminal justice settings (Nunn et al, 2009). These treatments have also been discouraged and stigmatized among some patient subpopulations, including those involved in 12-step mutual help programs (Frank, 2011; Rieckmann et al, 2014). Furthermore, patients may have residual symptoms during initiation of OAT or during agonist-assisted withdrawal, and may benefit from augmentation (Diaper et al, 2014), and augmentation with an α 2 -adrenergic agonist has been used to prolong abstinence in buprenorphine-maintained patients with a putative mechanism of amelioration of stress-induced relapse, consistent with its mechanism as a sympatholytic (Kowalczyk et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although methadone and buprenorphine are effective OATs for management of OUD, they are controlled substances with limitations that include restricted access and availability (Sharma et al, 2017), potential for misuse and diversion (Soyka, 2014), and barriers to acceptability in certain arenas, such as criminal justice settings (Nunn et al, 2009). These treatments have also been discouraged and stigmatized among some patient subpopulations, including those involved in 12-step mutual help programs (Frank, 2011; Rieckmann et al, 2014). Furthermore, patients may have residual symptoms during initiation of OAT or during agonist-assisted withdrawal, and may benefit from augmentation (Diaper et al, 2014), and augmentation with an α 2 -adrenergic agonist has been used to prolong abstinence in buprenorphine-maintained patients with a putative mechanism of amelioration of stress-induced relapse, consistent with its mechanism as a sympatholytic (Kowalczyk et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of buprenorphine dissemination have suggested that early buprenorphine clinical trials, with their support for staff training, provided the infrastructure for subsequent general adoption in those public hospitals that hosted trials (Rieckmann et al, 2014). We could not address this issue, as we lacked the data on which VHA facilities participated in such clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Stronger networks of buprenorphine providers have eased buprenorphine dispense in the past and can help improve the continuity of care for buprenorphine patients who are displaced from their primary clinic. 15 Such networks promise not only to enhanced cross-coverage during routine and emergency service disruptions, but also to address a widespread concern among current and potential buprenorphine prescribers about the lack of professional support and mentoring available to prescribers in managing buprenorphine patients. 16 During Hurricane Sandy, providers depended on the prescribing capabilities of residents and fellows, and credentialing delays for these trainees became increasingly cumbersome for continuity of care of patients at host hospitals.…”
Section: Discussionmentioning
confidence: 99%